Analysis of Environmental Care Character in Grade V Students in Elementary School - Rihadi, Rihadi; Marhayani, Dina Anika; Hendriana, Evinna Cinda (STKIP Singkawang, 2024)
This study aims to describe the character of environmental care in fifth grade students at State Elementary School 94 Singkawang. The research used is descriptive qualitative research. The subjects of this study were fifth grade students at State Elementary School 94 Singkawang. The subject of this research is the place, behavior, and activities of fifth grade students at State Elementary School 94 Singkawang. The results showed that the environmental care character of students at the time of observation on the indicator of cleaning the toilet was 94.74% in the very caring category, the indicator for cleaning the trash can was 100% in the very caring category, the indicator for cleaning the environment was 92.10% in the Very caring category. the indicator of beautifying classrooms and schools with plants is 94.73% in the very caring category, the indicator participating in maintaining plants in the school yard is 100% in the very caring category, and the last one participating in activities to maintain environmental cleanliness is 73.68% in the caring category. The overall percentage of the indicators of environmental care is 92.54% and according to the results of interviews with the category of very caring. Thus, the environmental care character of fifth graders at State Elementary School 94 Singkawang is very concerned..